2010
DOI: 10.1136/hrt.2009.188722
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of catheter ablation on left ventricular and right ventricular function in patients with frequent premature ventricular contractions and preserved ejection fraction

Abstract: Frequent PVCs can induce subtle cardiac dysfunction detected by speckle tracking imaging analysis in patients without apparent cardiomyopathy. RFCA can successfully eliminate PVCs and improve cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 26 publications
5
80
0
1
Order By: Relevance
“…Our ability to predict the site of origin of the PVCs on surface electrocardiography 65 and to safely access the right ventricular outflow tract and left ventricle (including the pericardium and the aortic cusp region) 66,67 and the use of advanced 3-dimensional mapping tools allows us to precisely localize the PVC foci. Short-term ablation success rates of between 70% and 90% have been reported 10,21,22,54 ; however, the long-term ablative outcomes remain to be studied. Alternative energy sources such as cryoablation may help improve the efficacy-safety profile as compared with traditional radiofrequency-based techniques.…”
Section: Catheter Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ability to predict the site of origin of the PVCs on surface electrocardiography 65 and to safely access the right ventricular outflow tract and left ventricle (including the pericardium and the aortic cusp region) 66,67 and the use of advanced 3-dimensional mapping tools allows us to precisely localize the PVC foci. Short-term ablation success rates of between 70% and 90% have been reported 10,21,22,54 ; however, the long-term ablative outcomes remain to be studied. Alternative energy sources such as cryoablation may help improve the efficacy-safety profile as compared with traditional radiofrequency-based techniques.…”
Section: Catheter Ablationmentioning
confidence: 99%
“…Other studies also found significant reduction in LV end-diastolic dimensions of between 2 and 8 mm, mitral regurgitation by 75%, and New York Heart Association functional class by nearly 1 class. 14,15,21 Wijnmaalen et al 54 described a significant improvement in radial, circumferential, and longitudinal strain after catheter ablation in patients with frequent PVCs and preserved LVEF. However, like with any invasive intervention, the risks of catheter ablation (whether endocardial or epicardial) must be balanced against any potential benefits.…”
Section: Catheter Ablationmentioning
confidence: 99%
“…Several studies have documented an improvement in LVEF following PVC ablation in nearly all patients along with significant reductions in LV enddiastolic dimensions of between 2 and 8 mm, mitral regurgitation by 75%, and New York Heart Association functional class by nearly 1 class (93,94,95). Significant improvement in radial, circumferential, and longitudinal strain after catheter ablation in patients with frequent PVCs and preserved LVEF has also been shown (96). Short-term ablation success rates of between 70% and 90% have been reported (97,98).…”
Section: Diagnosis and Managementmentioning
confidence: 93%
“…(30,31). PVC can not only cause LV dysfunction in patients with no underlying structural heart disease, but they can also worsen LV function in those with known cardiomyopathy and underlying scar (32,33). However, the pathophysiology behind PVC-mediated cardiomyopathy is unclear.…”
Section: Effects Of Turning Off Crt Following Successful Pvc Ablationmentioning
confidence: 95%